2023
DOI: 10.1101/2023.03.01.23286630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteins and transcriptional dysregulation of the brain extracellular matrix in Parkinson’s disease: A systematic review

Abstract: The extracellular matrix (ECM) of the brain is a dynamic structure made up of a vast network of bioactive macromolecules that modulate cellular events. Structural, organizational and functional changes in these macromolecules due to genetic variation or environmental stressors are thought to affect the cellular functions, and may result in disease. Most mechanistic studies to date usually focus on the cellular aspects of diseases and pay less attention to the relevance of the processes governing the dynamic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 147 publications
(194 reference statements)
1
5
0
Order By: Relevance
“…Transcriptome analysis and comparison between PD and control DA neurons indicate several intracellular and extracellular pathways that are dysregulated in PD. These include focal adhesion and ECM-receptor interaction which are commonly dysregulated in PD in this study and previous studies (26,27,79). These findings suggest a focus on the ECM and its strong involvement in PD.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Transcriptome analysis and comparison between PD and control DA neurons indicate several intracellular and extracellular pathways that are dysregulated in PD. These include focal adhesion and ECM-receptor interaction which are commonly dysregulated in PD in this study and previous studies (26,27,79). These findings suggest a focus on the ECM and its strong involvement in PD.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is consistent with several studies using PD model mice, which suggested that the early phenotype is a decrease in synaptic activity that progressed to motor dysfunction inmany later stages. Thus, monitoring synaptic activity may have a significant impact on the early diagnosis and prediction of PD onset (76)(77)(78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…Many pathways related to the brain ECM were dysregulated in all the neurological disorders that were considered. The ECM has emerged as a central focus in neuroscience [83, 84], recognized as an integral part of neural functions, especially synaptic regulation [85] [86]. Dityatev et al introduced the concept of the ’tetra-partite synapse’ that expands the traditional understanding of synaptic structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…and other neurodegenerative diseases such as Parkinson's [93][94][95][96] and schizophrenia [97][98][99]. Here we concentrated on the early developmental physiological alterations in 4 different ASD and epilepsy-related genes.…”
Section: Code Availabilitymentioning
confidence: 99%